Turgenev's love myth in Chekhov's prose - Собенников, Анатолий (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2016)
The article surveys how Ivan Turgenev’s love myth is deconstructed in Anton Chekhov’s prose works. The latter writer presents the myth more often than not in an ironic mode of narration. While Turgenev’s axiology is literary-centric, Chekhov confronts it with his knowledge of gender psychology and “the understanding of what you write about”.